Psychometrics Properties an Instrument for Gauge the Reflective Thinking in University Students - Crespo-Cabuto, Angélica (2019)
The research determined psychometrics properties of an instrument to gage the reflective thinking in the formative development of university students. For this research 263 university students participated, of which 220 (83.7%) were females (M age= 20, DE= 1.5 years old), and 43 (16.3%) were males (M age= 20, DE= 2.5 years old). The final result empirically supports scale to gage different factors, reflective compression, support reflective processes and demonstrations of reflective process (X2 = 20.08, gl= 8, *p < .001; X2/gl= 1.397; CFI= .96; RMSEA= .039; GFI= .90). In conclusion, the instrument can be used on the evaluation of reflective thinking thought in university students.